WORK ENGAGEMENT AND SELF-EFFICACY AS KEY PREDICTORS OF TEACHER PERFORMANCE: EVIDENCE FROM MADRASAH IBTIDAIYAH TEACHERS - Lia Nur Atiqoh Bela Dina; Bagus Cahyanto; Elvin Fauziyah Syakila Toha Putri (PD PGMI se Indonesia, 2026)
This study examines the structural relationship between work engagement, self-efficacy, and teacher performance among Madrasah Ibtidaiyah teachers in Malang City. A quantitative explanatory approach with a survey design was employed involving 191 teachers selected through proportional random sampling. The instruments used were the Utrecht Work Engagement Scale (UWES), the Teachers’ Sense of Efficacy Scale, and the Marzano Teacher Evaluation Model. Data were analyzed using Structural Equation Modeling (SEM). The findings indicate that work engagement significantly influences both self-efficacy and teacher performance. Self-efficacy also has a significant positive effect on teacher performance and partially mediates the relationship between work engagement and performance. These results highlight the central role of work engagement in enhancing teacher performance both directly and indirectly through self-efficacy. This study contributes to the literature by providing empirical evidence of the structural relationship among work engagement, self-efficacy, and teacher performance in the context of Madrasah Ibtidaiyah, emphasizing the importance of strengthening teachers’ psychological resources to improve professional performance.